KONSEP EDUPREUNEURSHIP DAN URGENSINYA BAGI LULUSAN PERGURUAN TINGGI - Muhammad Ilham Thayyibi; Subiyantoro Subiyantoro (JURNAL EDUSCIENCE (JES), 2022)
Every year, scholars in Indonesia have increased. Due to the lack of competence of undergraduate graduates, many of them are unemployed, then stigma and negative terms appear to unemployed graduates, namely educated unemployment, etc. Therefore, this study aims to determine how the concept of edupreneurship and its urgency for college graduates. The method used is qualitative with a library research approach. The data collection technique is the documentation technique. Edupreneurship comes from the words education and entrepreneurship which means education and entrepreneurship, so edupreneurship means entrepreneurial education, which is to introduce entrepreneurial concepts to instill an entrepreneurial spirit, including being creative, innovative, willing to take risks and highly competitive. In this way, university graduates are able to compete in the industrial world. Therefore edupreneurship is important to be taught in educational institutions and universities